PERANCANGAN PASAR SENI DI KABUPATEN KUBU RAYA - Amanda, Yasmine Alifia; Khaliesh, Hamdil; BR Gultom, Bontor Jumaylinda (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
West Kalimantan, the XIXth Tourist Destination Area, is home to arts and culture as its main attractions. However, there is no dedicated space for marketing artistic products and organizing artistic activities. So a design is needed that can support tourism potential in the trade sector in the form of the art market. The basic aim of this design is to produce a design for the art market in Kubu Raya Regency as a forum for buying and selling products and organizing art activities. The design process involves data collection, analysis, synthesis, and pre-design drawings and detailed engineering designs. The design uses a city walk concept to maintain continuity with the surrounding environment. The result is an area with three building masses: the reception building, the workshop and gallery building, and the art market building. These buildings are connected by a pedestrian path, offering facilities like creative art space, picnic area, street food area, and amphitheater. The building's shape adapts to the branding of Kubu Raya Regency, Rising Kubu Raya, applied to the facade with secondary skin with a muare wave motif.